2008
DOI: 10.1088/0031-9155/53/22/015
|View full text |Cite
|
Sign up to set email alerts
|

Real-time motion-adaptive delivery (MAD) using binary MLC: II. Rotational beam (tomotherapy) delivery

Abstract: TomoTherapy delivery is controlled by a planned, projection-wised leaf sequence (sinogram) that is optimized during treatment planning. In this paper, we developed a software solution for real-time motion compensation that delivers helical TomoTherapy plans without modifying the hardware and workflow of the TomoTherapy delivery system. Unlike the dynamic MLCbased method, our technique only requires instantaneous tumor positions, which greatly simplifies its implementation. This technique re-uses the planned si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…(3 samples), 154ms (4 samples) and 308ms (8 samples). These lengths were selected considering the typical latencies of commercial robotic radiotherapy systems: ∼ 77ms in VERO systems [2], ∼ 115ms in CyberKnife [13], ∼ 170ms in Tomotherapy [38] and latencies up to several hundred milliseconds for typical couch or multi-leaf collimator (MLC) tracking devices [13,9]. A comparative analysis was then carried out among 1) no prediction, Figure 5.…”
Section: Performance Analysismentioning
confidence: 99%
“…(3 samples), 154ms (4 samples) and 308ms (8 samples). These lengths were selected considering the typical latencies of commercial robotic radiotherapy systems: ∼ 77ms in VERO systems [2], ∼ 115ms in CyberKnife [13], ∼ 170ms in Tomotherapy [38] and latencies up to several hundred milliseconds for typical couch or multi-leaf collimator (MLC) tracking devices [13,9]. A comparative analysis was then carried out among 1) no prediction, Figure 5.…”
Section: Performance Analysismentioning
confidence: 99%
“…Thus, although our study provides a simple and clear rule to translate longitudinal motion into dosimetric error, interrupting the treatment is still clearly not a desired option. Other investigators have proposed motion adaptive TomoTherapy that (Lu 2008, Zhang et al 2007, 2004 modifies beam modulation and shuffles the dose delivery sequence to compensate for the intrafractional motion, but these methods were designed for cyclic breathing motion and were not tested for non-cyclic random motion.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the patients can be set up accurately initially, because of the prolonged treatment time in SBRT and its frameless nature, intrafractional motion can occur and affect the dose. The interplay between breathing motion and HT delivery was studied (Kissick et al 2005, 2008, Kanagaki et al 2007, and it was demonstrated that regular periodic motion in that direction only blurs the dose slightly and minimally affects the quality of treatment delivery (Kissick et al 2005, Kanagaki et al 2007. However, it was also shown that if the breathing motion is not completely regular but involves random baseline drifting, then undesired significant dose deviation can occur, and this is attributed to the similarity of time scales between the random baseline drifting and the time to deliver dose to a slice by HT (Kissick et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has been the leading cancer diagnosed and cause of cancer death for many years in China, with a rapidly increasing trend during the past several decades [1,2] The incidence rate of lung cancer in China is relatively high, but is increasing at a more rapid rate than in Western countries. Many risk factors, such as cigarette smoking and air pollution, have been proven as risk factors of the disease [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%